Analysis Study of Hadiths Towards the Fatwa Book on Several Issues by H.M. Arsyad Thalib Lubis - Yuslem, Nawir; Sulidar, Sulidar; Mukhlis, Mukhlis (International Journal of Social Service and Research, 2024)
This study delves into the analysis of Hadith in H.M. Arsyad Thalib Lubis' Fatwa Book, titled Some Problems, with a specific focus on investigating the status of the Sanad and Matan, as well as exploring the method of Fiqhul Hadith employed in the book. The primary inquiries include determining Sanad's status, Matan's status, and the Fiqh al-Hadith method employed by Arsyad Talib Lubis. The research utilizes a literature-based approach with a scientific and methodological orientation. The findings reveal that out of 154 hadiths in the book, 97 are Sahih, 34 are Hasan, 14 are Da'if, 1 is Munkar, and 8 are not found in the Mutun al-Hadith. The Matan's status affirms that the contained hadiths align with the principles of the Qur'an, hadith, Ijma', Qiyas, and commendable Muslim practices, encouraging their incorporation into daily worship. The Fiqh al-Hadith method outlined in the book encompasses understanding the hadith following Quranic instructions, considering background, situational conditions, and purpose, distinguishing between variable means and fixed ends, discerning expressions of haqiqi and majadzi, recognizing the distinction between the unseen and the real, and ascertaining the meaning of words in the hadith. These findings contribute to a nuanced understanding of Hadith analysis and offer valuable insights for scholars and practitioners of Islamic jurisprudence.